2008
DOI: 10.1124/jpet.108.143396
|View full text |Cite
|
Sign up to set email alerts
|

Increased Endothelial Nitric-Oxide Synthase Expression Reduces Hypertension and Hyperinsulinemia in Fructose-Treated Rats

Abstract: Endothelial dysfunction and decreased production of nitric oxide (NO) by endothelial NO synthase (eNOS) are implicated in the pathogenesis of hypertension and insulin resistance. Because the potential influence of increased eNOS expression/ activity on these parameters is unclear, the present study examined the effects of eNOS gene therapy on insulin resistance and blood pressure alterations in a fructose-induced hypertension model in rats. As predicted, 2 weeks of fructose consumption in the drinking water re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
62
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 39 publications
6
62
1
Order By: Relevance
“…16 Recently, Nguyen et al 14 showed an association among sugarsweetened beverages, serum uric acid levels, and SBP in a crosssectional analysis of 4867 adolescents who were between the ages of 12 and 18 years and had participated in the NHANES (1999 to 2004). Studies in animals suggested that fructose may raise BP via several mechanisms, including stimulation of uric acid, [17][18][19] inhibition of endothelial nitric oxide synthase system, 20,21 and stimulation of the sympathetic nervous system, 22 or by directly increasing sodium absorption in the gut. 23 Although uric acid has been shown to mediate fructose-induced hypertension in rats, we could not demonstrate a relationship between high fructose intake and serum uric acid levels in this study.…”
Section: Discussionmentioning
confidence: 99%
“…16 Recently, Nguyen et al 14 showed an association among sugarsweetened beverages, serum uric acid levels, and SBP in a crosssectional analysis of 4867 adolescents who were between the ages of 12 and 18 years and had participated in the NHANES (1999 to 2004). Studies in animals suggested that fructose may raise BP via several mechanisms, including stimulation of uric acid, [17][18][19] inhibition of endothelial nitric oxide synthase system, 20,21 and stimulation of the sympathetic nervous system, 22 or by directly increasing sodium absorption in the gut. 23 Although uric acid has been shown to mediate fructose-induced hypertension in rats, we could not demonstrate a relationship between high fructose intake and serum uric acid levels in this study.…”
Section: Discussionmentioning
confidence: 99%
“…5,[47][48][49] Thus, the finding that association of ISI-M with new-onset hypertension in the multiple logistic regression analysis was lost by incorporating BMI as a dependent variable (Table 4) does not necessarily exclude the possibility that IR per se contributes to the development of hypertension. In fact, OR of hypertension was higher in a subgroup with lower ISI-M than in a subgroup with higher ISI-M for each tertile of BMI in subjects o60 years old (Figure 3), whereas higher BMI was associated with higher OR of hypertension.…”
mentioning
confidence: 99%
“…5,[13][14][15][47][48][49][50] However, the contribution of any of these mechanisms has not yet been unequivocally demonstrated in human subjects. Acute hyperinsulinemia, induced by insulin infusion, has been shown to reduce urinary sodium excretion and to increase plasma norpeinephrine and renin activity, but it does not consistently elevate BP.…”
mentioning
confidence: 99%
“…Indeed, endothelial dysfunction and decreased production of nitric oxide (NO) by endothelial NO synthase (eNOS) is involved in the pathogenesis of insulin resistance and hypertension [21]. The polymorphic variants of the eNOS gene are associated with high blood pressure and insulin resistance in different populations [22].…”
Section: Discussionmentioning
confidence: 99%